Peningkatan Daya Saing Desa Wisata Alam Endah melalui Pendampingan Pembuatan Peta Jalur Wisata - Resista Vikaliana; Yelita Anggiane Iskandar; Nur Layly Rahmawati; Mirna Lusiani; Adji Candra Kurniawan; Rahmad Inca Liperda; Wegik Dwi Prasetyo; Epo Prasetya Kusumah; Ita Musfirowati Hanika; Ari Rahman; Muhammad Nur Ahadi (Journal of Social Responsibility Projects by Higher Education Forum, 2023)
Alamendah Village is a tourist village located in Bandung Regency, West Java. Alamendah or Dawala Village, has very high tourism potential and is famous for its natural beauty which is still cool and beautiful. Apart from that, Dawala is an agronomic or agriculture-based village. With this potential, Dawala can develop tourist villages to improve the welfare of village communities, so that they have a competitive edge. One strategy that can be used to increase the competitiveness of the tourism industry is to improve the quality of services, including mapping tourist routes in Dawala. Based on discussions and agreements with the partner of this activity (Dawala), assistance activities were carried out to create a tourist route map divided into several stages. These stages consist of: initial observations and surveys as well as FGDs, then discussion of implementation techniques, socialization and assistance in making tourist route maps, making tourist route maps, and soft launching. The implementation of mentoring activities was agreed to last for 1 year, namely in 2023. As a result, with the existence of a tourist map, it makes it easier for tourists to visit tourist attractions in Dawala and can motivate people in Dawala to participate more in the tourism potential in their village so that it is hoped that it can provide increasing the standard of living of its people.